Hubungan Persepsi Ibu dan Partisipasi Balita Ke Posyandu Dengan Kejadian Stunting Pada Balita Usia 36-59 Bulan Di Wilayah Kerja Puskesmas Gilingan Surakarta - Wahyuningtyas, Dhina Septria; , Dr.Mutalazimah,SKM.,MKes; , Luluk Ria Rakhma, S.Gz., M.Gizi (2015)
Stunting is linear growth delay. Among other affecting factors are mother perception and toddlers participation in integrated health service center. The mothers' perception will affect their behavior to bring their toddlers in integrated health service center, so that toddlers nutritional status height-for-age (TB/U) will be observed. To assess correlations mothers' perception and toddlers participation in integrated health service center with the incidence of stunting of toddlers at the age of 36-59 months at primary health center of Gilingan Surakarta. Quantitative research used cross-sectional design within 47 respondents who were selected through simple random sampling technique. Perception data were obtained through the interview, while toddlers participation is noted from integrated health service center data cadre and health care card (KMS). The analysis used both pearson product moment statistical test and rank spearman. The perception of most mother in integrated health service center is good (83%). Good participation of toddlers is 83%. Non-stunting toddlers is 76,6%. Mother of middle perception in integrated health service center in whose non-stunting toddlers is higher 87.5% compared to mother who has good perception which only 74,4%. Toddlers of good participation has higher non-stunting nutritional status (79.5%) compared to toddlers of unwell participation. There are no correlation mothers' perception in integrated health service center and the incidence of stunting (p=0,644). There are no correlation toddlers participation in integrated health service center and the incidence of stunting (p=0,183). There are no correlation mother perception and toddlers participation in integrated health service center with the incidence of stunting of toddlers at the age of 36-59 months in primary health center of Gilingan Surakarta.